1998
DOI: 10.1007/s002239900427
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Density with Normal Bone Turnover in Ovariectomized and Streptozotocin-Induced Diabetic Rats

Abstract: Diabetes and estrogen deficit are known causes of osteopenia, diabetes being associated with a low bone turnover and estrogen deficit with a high bone turnover. In the present work, we studied the effect of combined ovariectomy and diabetes on bone mineral content (BMC) and bone mineral density (BMD) and several bone markers in the rat. Four groups of rats were studied: control (C), ovariectomized (O), diabetic (D), and ovariectomized and diabetic (DO). Twelve weeks after starting the experiments, BMC and BMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
2
30
0
1
Order By: Relevance
“…These events include a decrease in osteoblast differentiation/maturation (1,55,56); an increase in adipocyte differentiation (10,15,55); an increase in monocyte/macrophage activation (57); an increase in bone inflammation (55, 57); and a decrease or no change in osteoclast number, erosion depth, and erosion surface (12,13,55,58). However, the mechanisms underlying diabetic bone mineral loss are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These events include a decrease in osteoblast differentiation/maturation (1,55,56); an increase in adipocyte differentiation (10,15,55); an increase in monocyte/macrophage activation (57); an increase in bone inflammation (55, 57); and a decrease or no change in osteoclast number, erosion depth, and erosion surface (12,13,55,58). However, the mechanisms underlying diabetic bone mineral loss are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients, decreased osteoblast function is thought to be associated with a defect of osteocyte maturation on the basis of normal serum levels of procollagen peptide, an early osteoblast marker, and decreased serum levels of osteocalcin, a late-stage marker of osteoblast maturation (10,11). The decrease in serum osteocalcin is even more pronounced in diabetic rat models (5,(12)(13)(14). These data suggest that a decrease in osteoblast number, function, and/or maturation may be a contributor(s) to bone loss in diabetes (10).…”
mentioning
confidence: 99%
“…1B and 1C). Herrero et al also showed no effect of OVX on serum glucose levels in streptozotocininduced diabetic rats [4]. These data suggest that OVX hardly affects glucose metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…High glucose condition decreased cell proliferation and osteocalcin secretion in human osteoblast-like MG-63 cells [5]. Bone loss associated with low bone formation was observed in rats with diabetes [4,16]. On the other hand, urine DPD levels were higher in SDT-fa/fa rats than in control rats 15-30 weeks after surgery (Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation